Dakwah Walisongo Di Jawa: Membangun Komunitas Muslim Multikultural - Rojikin Rojikin (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
In central Java, Sunan Kalijaga is the most famous of the wali. According to some accounts he was the inventor of the slametan, the Javanese wayang play, and the state ceremonies of Demak and Mataram. Islam in Java is by no means a waning religion but a vital living faith providing guidelines for ethics and inspiration for aesthetics; Islamization of Java is not a completed historical event but an ongoing process. Islam concerns not a particular segment of Javanese society but its entire population in that it constitutes an integral part of Javanese religious traditions. We know that social, political, economic and religious realities have changed dramatically in Java since the times of Geetz and of Nakamura’s own ealier research. Under the Walisongo leadership the pesantren tradition in the Pesisir of Java has been set up not only as the Islamic center for religious and socio-cultural studies for the Santri (religious student) who coming from everywhere in Java and Nusantara,but also as the center for social political basis of the Javanese Muslim society